Regulating Money Laundering and Tax Havens: The Role of Blacklisting - Unger, B.; Ferwerda, J. (UU USE Tjalling C. Koopmans Research Institute, 2008)
Since ten years, and more so, since September 11, 2001, international organizations such as the IMF, OECD and EU try to combat harmful tax competition, money laundering and terrorist financing. Blacklisting, the naming and shaming of uncooperative countries, was one of the strategies used from the very beginning of this new policy area. An analysis of the black listed countries over time shows, that the black lists got shorter and shorter over time. In 2006, Myanmar was the only country listed for money laundering, until it was finally also removed from the list. The paper wants to explore a) the reasons for removing large countries and especially EU countries from the list b) the wanted and unwanted effects blacklisting had for the named and shamed countries and discusses c) whether this necessarily means the end of blacklisting. We want to show d) a new way of greylisting which might be more compatible with the international diplomatic requirements. We developed a new indicator for rating countries with regard to cooperative behavior for tackling money laundering, which might also allow for benchmarking, a concept probably more accepted within the EU than blacklisting.
Keywords: Money Laundering; Tax Havens; Blacklisting; Naming and Shaming; SDG 16 - Peace, Justice and Strong Institutions